The Roles Performed by Consultants in Disseminating EMA in Philippines and the Need for New Approaches to Implement EMA - Ghosh, Biswaraj (2012)
Research on the dissemination of EMA from the developing country context undertaken previously focussed on the roles of government and accountants contributing to the diffusion of EMA. By focussing on consultancy literature to identify the diverse roles undertaken by external consultants, this research aims to explore the consultants’ roles in disseminating EMA in Philippines. With the focus on sustainable development and regulators in developing countries encouraging the private sector to undertake proactive environmental practices, the benefits of EMA tools and techniques in facilitating Clean Production practices is unparalleled. Given the state of EMA adoption in Philippines still at an early stage, the consultant’s roles as the Knowledge Transferer informing and educating clients on the benefits of EMA is crucial to its dissemination. Although there are significant measures adopted by government to encourage proactive environmental management practices within the private sector, the uptake of EMA has been limited largely due to ineffective enforcement of environmental regulations and managerial over reliance on traditional accounting approaches. As will be evident from the study, consultants have been encouraged to focus on their content focussed roles informing clients about limitations of the conventional accounting approaches and put emphasis on the benefits of EMA in facilitating sustainable environmental practices. The objective is to make clients appreciate EMA as an integral decision-making tool not to be treated in isolation for solely complying with regulations but to use it as a ‘tool-kit’ for sustainable decision-making. A new type of role referred to as “The Collaborator” has been identified in the context of the study. The role entails the consultant taking a proactive stance and working in partnership with local governments ‘acting as a bridge or a link’ between the government and the private sector with the objective of imparting knowledge about the ambitious goals of the regulators as well as educating the private sector about EMA tools and techniques through training programmes, presentations and provision of hard facts. Although, the use of reactive rhetorical strategies prevails, nonetheless, consultants are encouraged to use proactive rhetoric as the basis for providing justifications to convince clients to apply their recommendations.